Earned Income Tax Credit Plus: A New Way to House the Working Poor - Dreier, Peter (2024)
The housing affordability crisis is one of the defining features of the US today. The demand for housing subsidies outstrips supply by a factor of at least 4 to 1. Moreover, housing affordability varies greatly between and within metropolitan areas. This article proposes a new federal policy—the Earned Income Tax Credit (EITC) Plus—to decrease housing cost burdens for working households by combining aspects of two major federal programs, the EITC, a tax-based subsidy for low-income working households, and the Housing Choice Voucher, a subsidy that pays the difference between 30% of household income and rent. We propose an EITC housing supplement via the tax code for markets where income and current EITC benefits are below 30% of rent levels. It will reduce the housing affordability crisis and reduce the geographic disparities of the Housing Choice Voucher. We simulate the cost at $101 billion nationally (based on 2021 figures). Varying program rules and parameters can significantly reduce costs. Piggybacking on the EITC simplifies the proposal’s implementation and increases its political palatability.